ANALISIS MANAJEMEN PENGELOLAAN PERKEBUNAN KELAPA SAWIT PERSPEKTIF BISNIS ISLAM (STUDI KASUS: PETANI KELAPA SAWIT MUARA KIAWAI KABUPATEN PASAMAN BARAT) - Indra Pradana; Zuwardi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
The backgrounnd of this research is that oil palm farmers in managing oil palm plantations have not been maximizeed sothat it affects the quality of oil palm fruit and the ethics of oil palm farmers paying workers' wages noton tine. The purpose off this studiy was todetermine the management of coconut plantations and the management of oil palm plantations from the Islamic business perspective of Muara Kiawai, West Pasaman Regency. This researrch uses a qualitative descriptive research type. The tyipe of data use is primary data andsecondary data and uses data collectcion techniques by observatiion, interviewsand documentati. Based on the results of the study, the management of oil palm plantations in Muara Kiawai Pasaman Barat has not been maximized. Oil palm farmers in Muara Kiawai do not understand about their own nurseries and buy them at nurseries at quite expensive prices. Oil palm farmers do not know the planting time in planting oil palm. Hygiene maintenance around the oil palm was not paid attention to, they did not have plates and the farmers did not understand the dosage of fertilization. In controlling pests and diseases of oil palm farmers only allow pests and weeds to interfere. In the harvesting process, farmers harvest palm oil before it is time to harvest due to urgent circumstances that affect unproductive yelds. Therefore, optimal management is needed to increase crop yields. Complaints of oil palm farmers when the priceof palm oil is low and the price of fertilizer is getting higher, making farmers experience difficulties. Then the Islamic business ethics of oil palm smallholders in managing oil palm plantations results in delays in payment of wages to workers. This is notin accordance witth the objective ofthe principle of monotheism, which is to form a unified whole.